2010
DOI: 10.1029/2009gl041971
|View full text |Cite
|
Sign up to set email alerts
|

Multiple overshoot and rebound of a bursty bulk flow

Abstract: Chen and Wolf (1999) used a thin‐filament theory to construct a 2D model of a bursty bulk flow (BBF) motion inside the plasma sheet. The modeling revealed that the low‐entropy filament overshoots its equilibrium position and executes a heavily damped oscillation about that position. In this letter we demonstrate, for the first time, the multiple overshoot and rebound of a BBF observed by the five THEMIS probes on 17 March 2008 just after 10:22 UT. We found that the BBF oscillatory braking was accompanied by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
183
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 162 publications
(207 citation statements)
references
References 24 publications
24
183
0
Order By: Relevance
“…It can be suggested that the observed fast azimuthal flows are similar to the flow patterns in the near-Earth plasma sheet that were recently observed using mainly the THEMIS spacecraft [Keika et al, 2009;Keiling et al, 2009;Ohtani et al, 2009;Panov et al, 2010aPanov et al, , 2010b. For example, Panov et al [2010b] showed by means of five THEMIS probes covering radial distances between 15 R E and 9 R E that the fast earthward flow in the magnetotail was largely deflected and reversed its direction tailward because of the increase in the radial pressure gradient.…”
Section: Discussionmentioning
confidence: 70%
“…It can be suggested that the observed fast azimuthal flows are similar to the flow patterns in the near-Earth plasma sheet that were recently observed using mainly the THEMIS spacecraft [Keika et al, 2009;Keiling et al, 2009;Ohtani et al, 2009;Panov et al, 2010aPanov et al, , 2010b. For example, Panov et al [2010b] showed by means of five THEMIS probes covering radial distances between 15 R E and 9 R E that the fast earthward flow in the magnetotail was largely deflected and reversed its direction tailward because of the increase in the radial pressure gradient.…”
Section: Discussionmentioning
confidence: 70%
“…Using MHD simulations, Wolf et al [2012] showed that neglect of inertial effects in bubble-injection situations where they are not negligible does not prevent RCM-E from correctly predicting total magnetic-flux transport, magnetic dipolarization, and the associated particle energization, because bubbles would eventually stop at their equilibrium locations in their simulations. However, both Panov et al [2010] and Wolf et al [2012] showed that bubbles may overshoot and rebound around their equilibrium location. Therefore, we speculate that bubbles could penetrate deeper into the inner magnetosphere when effects of their overshoot were taken into account than not, which implies that the contribution of bubbles to the ring current energy may increase further.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of the induction electric field is associated with the magnetic field dipolarization, which is calculated self-consistently in the RCM-E. The increase of the potential electric field is associated with the buildup of charges on the edges of the bubble [e.g., Pontius and Wolf, 1990;Nakamura et al, 2001]. Therefore, we place a concentrated electric field along the sector of the boundary where the bubble is injected.…”
Section: 1002/2015ja021398mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Birn et al [2004], flow vortices appear at the flanks of the bubble, twisting the magnetic field, and causing a downward (upward) field-aligned current at the dawnside (duskside) flank, and forming a local wedge like current system [e.g., Wolf, 1993, 1999;Sergeev et al, 1996a;Birn and Hesse, 1996;Birn et al, 1999Birn et al, , 2004Snekvik et al, 2007;Zhang et al, 2009]. A return plasma flow may occur at the flanks of the bubble, and the corresponding shear against the plasma flow in the bubble main channel may also be involved in the generation of the field-aligned currents [e.g., Chen and Wolf, 1999;Kauristie et al, 2000;Birn et al, 2004;Keiling et al, 2009;Ohtani et al, 2009;Walsh et al, 2009;Panov et al, 2010aPanov et al, , 2010bBirn et al, 2011;Ge et al, 2011;Pitkänen et al, 2011].…”
Section: Introductionmentioning
confidence: 99%